2016
DOI: 10.1111/jnu.12239
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Violence and Health in Female University Students in Spain

Abstract: Prevention programs that promote harmonious social relationships among university students should be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
8
0
3
Order By: Relevance
“…This cross-sectional study used data from a previous Spanish survey that assesses the impact of violence on women university students' health (Martín-Baena, Talavera, & Montero, 2016). The sample was selected by a convenient approach among female students enrolled in the academic year 2013-2014 at the Nursing and Teacher Training Faculties of the University of Valencia.…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study used data from a previous Spanish survey that assesses the impact of violence on women university students' health (Martín-Baena, Talavera, & Montero, 2016). The sample was selected by a convenient approach among female students enrolled in the academic year 2013-2014 at the Nursing and Teacher Training Faculties of the University of Valencia.…”
Section: Methodsmentioning
confidence: 99%
“…Violence-related behaviours among adolescents and emerging adults may include in a physical fight [2,14], carried a weapon [2], handgun access [15], and injury [5,10]. Poor mental health as a consequence of physical IPV and/or sexual violence victimization among adolescents and emerging adults may include depression [5,9,11,12,[16][17][18][19][20], posttraumatic stress [5,11,12,16], anxiety [5,9,16,19], psychological distress [8,21], suicidal behaviour [2,14,17,20], sleep disorders [5,12,13], and disordered eating [5,10]. Several studies found that a history of physical IPV and/or sexual violence victimization among adolescents and emerging adults increased the odds for substance use, such as alcohol use or binge drinking [2,5,9,10,13], tobacco use [5,6], drug use [2,5,6,9,10,<...>…”
Section: Introductionmentioning
confidence: 99%
“…Patients report that pharmacists are one of the most trusted members of the health care team and utilization of the expanding pharmacy services continues to increase, including engagement in partnerships in public health [ 22 , 23 , 24 , 25 , 26 ]. Patients exposed to IPV are more likely to utilize prescription medications, including mental health and antihypertensive drugs [ 27 , 28 , 29 ]. Patients exposed to IPV are at greater risk for cost-related medication nonadherence and are less likely to utilize contraception [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%